BOOK REVIEW OF APICULTURE - EMMANUEL, KOYEU TATOU; GRACE, MENDI; XAVIER, TCHAMAGO FRANCOIS; CLOTEX, TAJEUKEM VICE; VALCIN, FRANKLIN; COLLAZO, LINDA (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
Apiculture can be defined as the keeping of bees especially for commercial purposes. The main countries concerned with the exportation of honey are found in Asia and South American countries while the main countries importing honey are Arabian countries, Japan, European countries, Canada and USA. As bee products, we have honey which is the transformation of saccharine into glucose sugar on the effect of invertase which contains the bees’ saliva; the royal jelly which contains water, proteins, amino acid, lipids and oligo-elements; pollen; wax; propolis; pollination etc Bees like most insects are divided into 3 major parts: the head, the thorax and the abdomen. Their principal organs are digestive system, the respiratory organ, the circulatory organ, the urinary system, the male reproductive organ, the female reproductive organ and the nervous system. Bees are special insects which have social organization. We have the queens, the workers and the drones. The queen has short wings, a long abdomen and an oval head. Apart from being the only egg layer in a normal hive, it is a source of important chemical messages, known as pheromones. The drones have to eat and take care of the queen. As for the workers, they take care of the ovaries and cleaning of the hive, and they also ventilate and warm up the hive. Talking of techniques of agriculture, we have fixed and mobile hives. At the harvest moment, the bee keeper wears a special dress in order to protect himself from stings of the insects. These are helmet or cap, gloves, boots … Concerning the installation of the bee hive, the zone must be rich in natural vegetation with harmless plants for the bees, reason why savanna and forest zones are better than mangroves and swampy zones because the honey produced in these zones are bitter. The hive should be installed during favorite and appropriate nutrition periods and it should be comfortable. The support should not be accessible by predators like termites, rats; the hive should be suspended, the hives should have a space of at least 50 cm from each other with different orientation and we should take note of the entry hole because it should not be big East – South – East orientation are preferable so as receive the morning solar rays. Bees face diseases which can be anatomic, physiologic or behavioral. Here, we have decisive and favourable causes. In harvesting honey we have to be very delicate, smooth and swift. After that, we proceed to filtering, and packaging honey